THE VALUES OF SUFISM IN QASIDAH OF NASIDA RIA - Zahriyanti; Sopar (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
In the teachings of Sufism, training that must be taken by a person, namely takhalli, tahalli, and tajalli. When viewed in term of it is content, many of Qasidah’ Nasida Ria's poems that contain the subject of monotheism, the greatness of Allah swt, about the histories of world peace, salawat to the Prophet, honesty, about halal and haram,repentance, etcetera. As to formulation of the problem in this research is, How are the values of Sufism that is contained in the poems of Qasidah’ Nasida Ria? The purpose is to know the values of Sufism contained in the poem of Qasidah’ Nasida Ria.The method is used a qualitative approach. This type is Library Research. The data collection technique is documentation. The descriptive analysis that used is content analysis. The result of research is that the values of Sufism in the Qasidah’ Nasida Ria poems are Takhalli, such as enmity, murder, indulgence in lust, eating unlawful food, always living in sin. Tahalli values, such as repenting, sincerely seeking knowledge, steadfast, patient, resignation, honest, heartfelt in trials, imitate the moral of the Prophet, use and eat what Allah has made lawful for. The value of Tajalli such as a true happiness, willing with Allah's provisions, keeping and maintaining the Shari'a, easy to get Allah's knowledge.